Theorising children’s participation: Trans-disciplinary perspectives from South Africa - Patricia Henderson; Shirley Pendlebury; E. Kay M. Tisdall (Perspectives in Education, 2011)
From text: Children’s participation is a popular rallying cry among child rights activists and community development groups, backed by the recognition of children’s participatory rights in the United Nations Convention on the Rights of the Child (UNCRC). Participation is both a guiding principle of the UNCRC and an explicit right. Article 12 establishes the right of children (who are capable of forming their own views) to express them freely in all matters affecting the children, and for their views to be given due weight, in accordance with age and maturity. In South Africa, children’s participatory rights are recognised in the Children’s Act, the Child Justice Act and, in a more circumscribed way, the South African Schools Act.